Is There a Difference in Terms of Perinatal Outcomes Between Fresh and Frozen Embryo Transfers? - Ayse Zehra Ozdemir; Pervin Karli (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Nowadays, fresh embryo transfers and frozen embryo transfers are frequently employed in the treatment of in vitro fertilization. This study aims to compare the pregnancy outcomes in patients who underwent fresh embryo transfers and frozen embryo transfers.